Intercultural Theology KH. Hashim Asy'ari: Memadukan Kebudayaan, Keislaman, dan Nasionalisme di Indonesia - Achmad Muhibin Zuhri (Indonesian Journal of Humanities and Social Sciences, 2020)
Religion has two inherent characteristics. It will be transcendent if it is expressed as servitude to God. However, it becomes profane when articulated into fellow human beings' lives. Thus, religion cannot be separated from the influence of the culture in which humans exist. Through an intercultural theological approach, this study intends to show the thoughts of Kiai Hashim Asyari, who can integrate Sunni theological discourses relevant to Indonesian society's culture without reducing the fundamental values of faith. This study argues that Kiai Hashim's view of theological discourse can be introduced as the idea of "local theology." Adopting the historical research method of critical thinking and the approach of intercultural studies revealed that the concept of intercultural theology in Kiai Hashim's thought is a strategy to contextualize Islam. Its relevance in Indonesia, Islamic theology has been successfully articulated not only limited to ritual sacraments but also appreciative of local elements, as well as contributing to developing a spirit of nationalism. The style of theology shown by Kiai Hashim can be seen as genuine, bearing in mind that theological discourse tends to be exclusive, which must follow its origins complete with cultural and social settings without considering the existing local character. With this religious style, its adherents can be contextual and relevant.